Assessment of cochlear trauma and telemetry measures after cochlear implantation: A comparative study between Nucleus® CI512 and CI532 electrode arrays - Domenico Cuda; Alessandra Murri (Audiology Research, 2019)
The aim of this study was to compare the new Cochlear™ Nucleus® Profile with Slim Modiolar Electrode (CI532, Cochlear Ltd., Sidney, Australia) with the previous Contour Advance® (CI512) implant through postoperative residual hearing (RH) threshold shift and telemetry measurements as indirect measures of cochlear trauma. We compared 21 patients implanted with the CI532 and 20 patients implanted with the CI512, matching the 2 groups for age and for hearing loss etiology. All subjects received audiological pure tone average (PTA) calculation pre- and postimplant. Electrode impedance was measured, followed by AutoNRT® to measure and evaluate the Neural Response Telemetry (NRT®) thresholds. Telemetry recordings were made intraoperatively, one month after surgery and one month after activation. The NRT-Ratio was calculated to evaluate full scala tympani (ST) insertion. The results showed a higher number of patients with preserved measurable hearing with the CI532 (10/15; P>0.05) compared to the CI512 (5/14; P<0.05). A significant difference in post-operative low frequency PTA was observed between the two groups. There were no significant differences for telemetry measurements and NRTRatio evaluation of full ST insertion (CI512: 81%; CI532: 95%). A significantly higher number of patients who preserved measurable hearing with the CI532, and a significantly higher post-operative low frequency PTA threshold compared with the CI512 confirmed better RH preservation and lower apical cochlear damage with the CI532. There was a high number of full ST insertions for both electrode arrays. Future studies should investigate the audiological effect of implantation in patients with higher levels of RH, correlating the results with the scalar position, to assess any lesser trauma of the CI532.